2016
DOI: 10.1016/j.tgie.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy and cross-sectional imaging for assessing Crohn׳s disease activity

Abstract: Crohn’s disease (CD) is principally characterized by chronic and recurrent inflammation of the gastrointestinal tract, most commonly found in the ileo-colonic region. The chronicity and severity of intestinal inflammation together contribute to progressive, cumulative, deep, transmural intestinal damage, including stricturing, obstruction, abscesses, and fistulae. Both intestinal inflammation and its chronic complications result in a range of symptoms subsequently leading to patient presentations with diarrhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Clinical studies evaluating efficacy of antifibrotic drug candidates in stricturing CD will face specific challenges. First, in contrast to luminal inflammation, in which severity of endoscopic lesions and severity of transmural changes assessed by cross-sectional imaging closely correlate,12 in stricturing lesions, routine endoscopic examination of the mucosa is insufficient for an accurate diagnosis. Biopsies are only superficial and not all strictures are accessible by endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies evaluating efficacy of antifibrotic drug candidates in stricturing CD will face specific challenges. First, in contrast to luminal inflammation, in which severity of endoscopic lesions and severity of transmural changes assessed by cross-sectional imaging closely correlate,12 in stricturing lesions, routine endoscopic examination of the mucosa is insufficient for an accurate diagnosis. Biopsies are only superficial and not all strictures are accessible by endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction in the late 1960s, the CDAI has become the most commonly utilized tool for the assessment of clinical activity in Chron's disease [15] . However, previous reports demonstrated that CDAI poorly predict the clinical behavior and treatment response in Chron's disease [16] .…”
Section: Discussionmentioning
confidence: 87%
“…5 Clinical trials in CD have used disease indices such as the Crohn's Disease Activity Index (CDAI) 6 as primary endpoints, but both health authorities and investigators have recognized a need for more objective measures of treatment response. 7 One such measure is based on the appearance of the mucosa as visualized by video ileocolonoscopy, 8 and endoscopic mucosal healing has been associated with improved long-term outcome in CD. Considerably less is known about the clinical relevance of achieving histologic remission or the relationships among histologic, clinical, and/or endoscopic measures of CD.…”
Section: Methodsmentioning
confidence: 99%